PEMETAAN AKTIVITAS TRIDARMA PROGRAM STUDI AKUNTANSI UNIVERSITAS ISLAM INDRAGIRI DALAM PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Rosliana . (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
Accounting Study Program of Islamic University of Indragiri (UNISI) was founded in 2008 with acreditation B which commited as member of SDGs law pillar and governance working group. The purpose of this research is to view the alignment of SDGs with TRIDAMA activities of Accounting Study Program of Islamic University of Indragiri (UNISI) in order to support the SDGs achievement. SDGs are 17 goals, 169 targets and 241 indicators in social dimension coverage, economic and environment, law and governance. Based on desk review, it can be concluded that the Accounting Study Program of Islamic University of Indragiri (UNISI) could provided the achievement acceleration of 16 goals; peace, justice and the formidable institutional which distributed in 4 indicators of SDGs